Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat Di Kecamatan Mandalajati Kota Bandung - Akbar, Muhammad Husni; Kartini, Entin; Barokah, Rezky Afiahtul (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
The state apparatus is expected to provide the best possible service to the community in various ways. One thing that needs attention is the public service sector, especially in terms of the quality or quality of service provided by government officials to the public. This study aims (1) to determine and analyze the quality of service in Mandalajati District, Bandung City; (2) to find out and analyze community satisfaction in Mandalajati District, Bandung City; and (3) to determine the influence of service quality on community satisfaction in Mandalajati District, Bandung City. The method used uses a quantitative approach, with the aim of measuring and understanding the causal relationships between variables (Creswell: 2009). The survey method is also used in obtaining data through various data collection techniques such as direct interviews, distribution of questionnaires, observation or observation. The results of the analysis say that service quality has a significant influence on community satisfaction.